Overall requirements in caregivers of people experiencing disability - Buitrago Echeverri, María Teresa; Pontificia Universidad Javeriana (Pontificia Universidad Javeriana - Facultad de Enfermería, 2011)
Objective: To identify the general necessities of a group of custodians of handicapped people at the Fontibon country (Bogotà, Colombia), in order to propose strategies of accomplishment that allow to contribute to the welfare of the custodians and also for the handicapped people. Materials and methods: This is a qualitetive study prformed between January of 2008 ans August of 2009 assessed the perceptions of the necessitiesdescribed under the "Social Determination of Health" model classifies as general necessities with the information regardign a group of informal custodians of hadicapped people, the family of the custodians, a team of professionals from the group of prevention and conducting of handicap that belongs to the Hospital of Fontibon Country and also involved representatives of instutions related to any type of disabilities. The tools used werw insight interviws, semi-structured interviews and focus groups. ResultsIn the voice of the participants there was found very often the financial necesities, the weaknessessof the social healthcare system, the problems related to access to healthcare, and the quality of the services, and also the lack of job opportunities. Conclusions: Even though the participants admitted that there has been some progress on the making of public policies related to handicapped people, they also perceive that this progress do not pertains to the custodians. Furthermore they manifest serious weaknesses in the structure of most of the aresa observed that shows the imperative necessity of putting collective effords together that allow to create integrated programs focused on the welfare of the custodians and also the handicapped people.